Efeitos da insuficiência renal aguda sobre o esvaziamento gástrico e trânsito gastrintestinal de líquido em ratos acordados - Silva, Ana Paula Teixeira da (2003)
Renal failure leads to important gastrointestinal functional changes. However, there are only few studies focused on the relationship between renal failure and gastrointestinal tract physiology. In this work we studied the gastric emptying (GE) and gastrointestinal (GI) transit of liquid 6, 12 and 24hr after awake rats had one or both kidneys surgically removed. In both experimental protocols, GE and GI transit were measured according to Reynell & Spray procedures. GE and GI transit were significantly reduced 6, 12 and 24hr after both kidney removal. Removal of only one kidney had no effect on GE and GI transit. Blood volume was greatly increased after bilateral kidney removal as well as plasmatic urea and creatinine levels. We also evaluated whether this phenomenon was caused by azotemia. In a separate group of animals, we observed that urea and creatinine infusions had no effect on GE and GI transit in intact animals. In addition, bleeding up to 30% of blood volume reversed GE and GI transit inhibitions in animals submitted to bilateral kidney removal. In summary, bilateral nephrectomy leads to GI motility inhibition, which seems to be due to hypervolemia and not to post nephrectomy azotemia.